Controlled Prelithiation of PbS to Pb/Li2S for High Initial Coulombic Efficiency in Lithium Ion Batteries. Issue 10 (1st January 2019) - Guo, Alan; Chen, Eric; Heller, Adam; Mullins, C. Buddie
Abstract : PbS nanoparticle aggregates were synthesized in a simple aqueous reaction at room temperature, and were tested as a lithium ion anode material, with a gravimetric capacity of 374 mAh/g at C/2, and a 0.15% capacity loss per cycle. However, its half cell initial Coulombic efficiency (ICE) was only 40%, due to a combination of irreversible Li2 S and solid electrolyte interface (SEI) formations. A custom controlled prelithiation technique was then applied to the PbS electrodes, converting the active material to Pb/Li2 S, and consolidating the SEI prior to coin cell assembly. This brought the ICE from 40% to >97%, and allowed for immediate cycling of the electrode at high Coulombic efficiency, without further formation cycles. Upon construction of prelithiated Pb/Li2 S vs NCM full cells, an 82% ICE was observed, with the majority of the lithium loss from the NCM. The full cells had a combined electrode capacity of 100 mAh/g at C/2.